Complete chloroplast genome sequence of Scurrula notothixoides (Loranthaceae): a hemiparasitic shrub in South China - Yuan, Lang-Xing (Mitochondrial DNA B Resour, 2018)
Scurrula notothixoides (Loranthaceae) is a hemiparasitic shrub distributed in forest margins of Southeast Asian countries. Here, we report and characterize the complete plastid genome sequence of S. notothixoides in an effort to provide genomic resources useful for the phylogenetic studies for Santalales. The complete plastome is 123,810 bp in length and contains the typical structure and gene content of angiosperm plastomes, including two inverted repeat (IR) regions of 23,101 bp, a large single copy (LSC) region of 71,448 bp and a small single copy (SSC) region of 6160 bp. The plastome contains 88 genes, consisting of 61 unique protein-coding genes, 23 unique tRNA genes and four unique rRNA genes. The overall A/T content in the plastome of S. notothixoides is 62.7%. Phylogenetic analyses were performed using the entire plastome, including spacers, introns, etc. and we recovered that S. notothixoides and Taxillus sutchuenensis was closely related. The complete plastome sequence of S. notothixoides will provide a useful resource for the phylogenetic studies for Santalales.